KAJIAN KELIMPAHAN MIKROPLASTIK PADA SEDIMEN DI WILAYAH INDONESIA - Diah Ayu Ambarsari; Milani Anggiani (Pusat Penelitian Oseanografi LIPI, 2022)
Microplastic pollution in the ocean is a type of hazardous waste. Microplastics are defined as plastic particles with a microscopic size of less than 5 mm. Generally, easy-to-find microplastics include fragments, films, and fibers. Microplastic fibers and fragments are classified as secondary microplastics derived from plastic fragmentation. The high abundance of this type of fragment is due to the predominance of waste on the riverbanks, such as plastic bottles or other household plastic waste, which is the source of these microplastic fragments. Meanwhile, microplastics with a high fiber content are caused by fishing activities such as degrading fishing lines and nets or by sources of waste from human activities that enter the river flow and settle in the sediment. Microplastics research is concentrated in western Indonesia, with only a few studies conducted in eastern Indonesia. This is because western Indonesia is more densely populated, implying that more plastic waste will be generated. As a result, research on the distribution and abundance of microplastics in sediments should be expanded, particularly in eastern Indonesia. It is necessary to conduct more thorough research on microplastics on the Indonesian mainland.